Political Demography and the Future of Kurdish Identity in the Disputed Areas of Iraq - Palani, Prof. Dr. Ibraheem. Q.; Karim, Dr. Muhammad Mahdi (Sulaimani Journal for Humanities, 2025)
Political demography is concerned with the interaction between the spatial dimensions of politics and social behavior, and the resulting demographic transformations driven by local and regional political actors, along with social structures, and their repercussions on issues of development and identity, as well as armed violence. This study sheds light on the relationship between the demographic dynamics of the disputed territories, as defined by Article (140) of the Permanent Iraqi Constitution, represented by fertility rates, migration (forced and voluntary), and terrorist operations, and the impact of these changes on shaping the Kurdish identity in the study area. To achieve the study's objectives, it was divided into a foundational approach to the concept of the state in Iraq, followed by a geohistorical examination of demographic changes and the main actors involved. The decline in the demographic size of the Kurds became clear through comparing the percentage of their population to the total population of Iraq. After constituting 16.7% according to the 1957 census, this percentage decreased to 13.8% in the 1977 census, a significant decrease of approximately 3%, yet it continued to dominate the trajectory of the Kurdish ethnic composition in Iraq. The study relies on the historical method and the political demographic approach to examine these changes. It relies on official statistics and surveys, as well as a set of maps using geographic information systems.
Keywords: Political demography; disputed territories; Kurdish identity